Oral Health Education Poster Competition 2015 by Department of Community Dentistry at BUMDC - Raima Bashir; Kulsoom Fatima Rizvi (Journal of Bahria University Medical and Dental College, 2021)
The Department of Community Dentistry of Bahria University Medical & Dental College, organized a students’“Oral Health Education Poster competition”on Wednesday 7th Oct 2015 from 9am to 2pm at the Ibn - e -Sina auditorium of BUMDC. The program was headed by Dr. Kulsoom Fatima Rizvi (Head of Department) and hosted by Dr. Raima Bashir and Dr. Anum Sami (lecturers of the department).The event commenced by display of scientific posters on a variety of topics relating to Community Dentistry and pertaining to oral conditions like xerostomia, baby bottle tooth decay, dental anxiety, prevention strategies and various other topics like cosmetic dentistry, which were prepared and presented by the 2nd Year BDS students. The whole Class had been divided into 14 groups which were supervised by Dr.Raima and Dr.Anum Sami. The Director General of BUMDC Vice Admiral (Retd) Tehseenullah Khan and Dean & Principal Health Sciences, Brig (Retd) Dr. Shaheen Moin were invited as chief guests. Respectable heads and faculty of entire medical & dental sections of BUMDC as well as guests from other Medical & Dental Colleges were also invited to provide support and encouragement to the participants. The Jury comprised of Dr Ashar Afaq (HOD Community Dentistry &Vice Principal of DUHS OJHA campus), Dr Mariam Azfar(HOD Community Dentistry, JSMU), Dr Ambreen Usmani (HOD Anatomy BUMDC) and Dr Mushtaq Memon (HOD Periodontology/Oral Medicine BUMDC) who judged each poster on their concept, knowledge, and presentation skills and scored them accordingly. The results were then compiled by commutating the marks allotted by each jury member. Every one appreciated the efforts of the students and shared their expert opinions and knowledge with them.